Ascorbate sensitizes human osteosarcoma cells to the cytostatic effects of cisplatin. Issue 4 (29th July 2020) - Oka, Naohiro; Komuro, Akiyoshi; Amano, Hisayuki; Dash, Suman; Honda, Masahiko; Ota, Kazushige; Nishimura, Shunji; Ueda, Takeshi; Akagi, Masao; Okada, Hitoshi
Abstract: Osteosarcoma (OS) is the most common malignant bone tumor and a leading cause of cancer‐related deaths in children and adolescents. Current standard treatments for OS are a combination of preoperative chemotherapy, surgical resection, and adjuvant chemotherapy. Cisplatin is used as the standard chemotherapeutic for OS treatment, but it induces various adverse effects, limiting its clinical application. Improving treatment efficacy without increasing the cisplatin dosage is desirable. In the present study, we assessed the combined effect of ascorbate on cisplatin treatment using cultured human OS cells. Co‐treatment with ascorbate induced greater suppression of OS cell but not nonmalignant cell proliferation. The chemosensitizing effect of ascorbate on cisplatin treatment was tightly linked to ROS production. Altered cellular redox state due to increased ROS production modified glycolysis and mitochondrial function in OS cells. In addition, OS cell sphere formation was markedly decreased, suggesting that ascorbate increased the treatment efficacy of cisplatin against stem‐like cells in the cancer cell population. We also found that enhanced MYC signaling, ribosomal biogenesis, glycolysis, and mitochondrial respiration are key signatures in OS cells with cisplatin resistance. Furthermore, cisplatin resistance was reversed by ascorbate. Taken together, our findings provide a rationale for combining cisplatin with ascorbate in therapeutic strategies against OS.